2019
DOI: 10.1039/c9nr03823j
|View full text |Cite
|
Sign up to set email alerts
|

Ferritin variants: inspirations for rationally designing protein nanocarriers

Abstract: Ferritin is endowed with a unique structure and the ability to self-assemble. Besides, genetic manipulation can easily tune the structure and functions of ferritin nanocages, which further expands the biomedical applications of ferritin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 81 publications
0
38
0
Order By: Relevance
“…[ 26 ] In addition, ferritin nanocages can be robustly produced by biological system (e.g., Escherichia coli ( E. coli ) system) with uniform size and unique structure, and can be modified with additional targeting motifs through genetic engineering, making it a promising candidate for tumor‐targeting drug delivery system. [ 27,28 ] However, limited by the hydrophilic nature of soluble protein, it has fallen short of achieving the objective to effectively load hydrophobic drugs, which are usually eliminated rapidly from the body and have low bioavailability. [ 29 ] Upload of both hydrophilic and hydrophobic drugs on one protein nanocarrier posts additionally challenges.…”
Section: Introductionmentioning
confidence: 99%
“…[ 26 ] In addition, ferritin nanocages can be robustly produced by biological system (e.g., Escherichia coli ( E. coli ) system) with uniform size and unique structure, and can be modified with additional targeting motifs through genetic engineering, making it a promising candidate for tumor‐targeting drug delivery system. [ 27,28 ] However, limited by the hydrophilic nature of soluble protein, it has fallen short of achieving the objective to effectively load hydrophobic drugs, which are usually eliminated rapidly from the body and have low bioavailability. [ 29 ] Upload of both hydrophilic and hydrophobic drugs on one protein nanocarrier posts additionally challenges.…”
Section: Introductionmentioning
confidence: 99%
“…[68] It is also reported that genetic manipulation can be firmly tuned for functional ferritin nanocages which expand biomedical applications of ferritin. [69] The basic difference between the protein-based nanocage as cargo for intracellular delivery and that of the MOF-based protein carriers is that EMP NPs not only protect the protein cargoes but also indulge in the phagocyte-dependent clearance of cargoes by selectively targeting the tumor site. [70,71] In general, when MOFs act as immobilizers and storage of functional proteins, they stimulate from the mesoporous structure that allows high protein loadings, including a framework architecture for providing both chemical and thermal stabilities for encapsulated proteins.…”
Section: Protein Nanocages Versus Mof-biomolecule Npsmentioning
confidence: 99%
“…The outer and inner diameters of ferritin cages are 12 and 8 nm, respectively, and they also carry a central cavity to store iron [16]. One of the reasons ferritin is so useful for biological applications is because the surfaces of ferritin, including the inner, outer, and inter-subunit interfaces, are amenable to different types of modifications [20,21].…”
Section: Introductionmentioning
confidence: 99%